Le testament de Louis de Bourbon-Vendôme, évêque d’Avranches (1510) - Vincent Tabbagh (Tabularia)
Legitimate son of a prince, reforming bishop, philanthropist and humanist, Louis de Bourbon-Vendôme left in 1510 a testament in which he shows little interest in veneration of saints, perpetual foundations and charitable bequests. However to assure his own salvation by the grace of his consecration, to constitute as many relics from three parts of his body, head, heart and bones, he asked to be dismembered.